An Ethnophysics Exploration of Traditional Marble Games: Analysis of Momentum and Impulse Concepts - Talitha Rizki Salsabila; Habibi Habibi; Luna Syarifa Nathania (Prodi S2 Pendidikan Fisika Universitas Negeri Surabaya, 2026)
Physics learning is often perceived as abstract and less relevant to students’ daily lives, resulting in low motivation and conceptual understanding. One approach that can overcome this problem is ethnophysics, which integrates physics concepts with local culture and traditional activities. This study aims to explore the concept of momentum in traditional marble games through an ethnophysics approach. This research used a qualitative descriptive method with an exploratory design. Data were collected through observation, documentation, and literature studies related to ethnophysics, traditional marble games, and momentum concepts. The novelty of this study lies in the specific analysis of momentum concepts in traditional marble games, which has rarely been explored in previous ethnophysics studies. The results showed that momentum and Impulse concepts appear during the movement and collision of marbles in the game. The magnitude of momentum is influenced by the mass and velocity of the marbles, where larger marbles produce greater momentum and faster-moving marbles generate stronger collisions. These findings indicate that traditional marble games can be used as contextual and meaningful physics learning resources on momentum concepts. This study contributes to the development of ethnophysics-based learning through the integration of local culture into physics education.